Genesis of peruvian coal in the global tectonic framework - Dunin-Borkowski, Estanislao (2007)
The Peruvian coal deposits have been formed along the continental ridge in three different important short times of the Peruvian geology history. The genesis is an indicator for the weather, geomorphology and the local geography latitude, and indirectly to the continental derive, regional tectonic and eustatic variation of the level of sea during the Phanerozoic, each of these times is related to the Peruvian tectonic development and mainly with the continental derive and the lineaments with the plate tectonics. The main causes of genesis of Peruvian basin coals were during each formation time, different, been all these basin subparallel to the continental ridge that was originally Gondwana and it belongs actually to South America, that is why the coal basins give an integral vision of the Peruvian geology in the Global Geotectonic.